Kannustinloukut suomessa - Päivi Puonti; Eija Kauppi; Mauri Kotamäki; Olli Ropponen (The Research Institute of the Finnish Economy (ETLA), 2022)
We analyze the impact of the Finnish tax-benefit system on the financial incentives to take up a job and to work more. The analysis is conducted with the Finnish microsimulation model SISU in 2015-2021. We analyze the presence of unemployment traps in the population and characterize the population subgroups associated with low work incentives. According to our results, the median participation tax rate in Finland is 69 percent, meaning that for half of working-age Finns the disposable income when in work increases by at most one third of the wage when employed. On average, the financial incentives to work of individuals receiving earnings-related unemployment benefits are lower than of those receiving flat-rate unemployment benefits, and the incentives of individuals receiving child home care allowance are better than the incentives of unemployed. Most of the individuals in unemployment trap receiving flat-rate unemployment benefits are beneficiaries of social assistance. In year 2021, 136,500 Finns found themselves in an unemployment trap defined as a situation in which disposable income increases at most 20 percent of gross income when employed. The amount of people in unemployment trap amounts to more than 300,000 when 25 percent is used as the relevant limit. Financial incentives to work have slightly improved since 2015. More than half a million Finns lose more than 50% of extra income due to tax increase and benefit withdrawal. The earnings disregard for basic social assistance improved the financial incentives to work of individuals in the lowest income group.
Keywords: J20; J22; H20; 330; Participation tax rates; Incentives to work; Microsimulation; Tax-benefit system